2011
DOI: 10.4103/0971-5916.92642
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to ART adherence & follow ups among patients attending ART centres in Maharashtra, India

Abstract: Background & objectives:Adherence to ART is a patient specific issue influenced by a variety of situations that a patient may encounter, especially in resource-limited settings. A study was conducted to understand factors and influencers of adherence to ART and their follow ups among patients attending ART centres in Maharashtra, India.Methods:Between January and March 2009, barriers to ART adherence among 32 patients at three selected ART centres functioning under national ART roll-out programme in Maharashtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 15 publications
1
17
1
Order By: Relevance
“…Social support has been associated with higher adherence (Nyamathi et al, 2012; Shah et al, 2007), and depression is linked with poorer adherence (Anuradha et al, 2013; Nyamathi et al, 2012; Sarna et al, 2008). Although stigma has been associated with poor adherence in many settings (Kingori et al, 2012; Rao, Kekwaletswe, Hosek, Martinez, & Rodriguez, 2007; Rintamaki, Davis, Skripkauskas, Bennett, & Wolf, 2006; Vyankandondera et al, 2013) and noted as a barrier in qualitative studies (Joglekar et al, 2011; Kumarasamy et al, 2005), it has not been quantitatively assessed in India.…”
Section: Introductionmentioning
confidence: 99%
“…Social support has been associated with higher adherence (Nyamathi et al, 2012; Shah et al, 2007), and depression is linked with poorer adherence (Anuradha et al, 2013; Nyamathi et al, 2012; Sarna et al, 2008). Although stigma has been associated with poor adherence in many settings (Kingori et al, 2012; Rao, Kekwaletswe, Hosek, Martinez, & Rodriguez, 2007; Rintamaki, Davis, Skripkauskas, Bennett, & Wolf, 2006; Vyankandondera et al, 2013) and noted as a barrier in qualitative studies (Joglekar et al, 2011; Kumarasamy et al, 2005), it has not been quantitatively assessed in India.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to other studies that show that the presence of family may promote nonadherence (Joglekar et al, 2011;Sharma, Khadga, Dhungana, & Chitrakar, 2013), the fact that one participant in this study noted the opposite is noteworthy. As Jadidi and Nakhaee (2014) assert, substance abuse can be promoted by one's peers as their association together yields more opportunities to engage in the behaviour (Jadidi & Nakhaee, 2014).…”
Section: Psychological Supportcontrasting
confidence: 41%
“…A systematic review by Govindasamy et al (2014) found several other interventions to be effective in facilitating linkage in LMICs including integration of care and point-of-care CD4 count. Moreover, while not addressed in this study, discrimination by healthcare providers, threat of jail, or criminal prosecution, as well as travel or waiting time, could be additional barriers for MSM and PWID in accessing appropriate HIV-related health care (Chakrapani et al, 2011, 2014; Joglekar et al, 2011). …”
Section: Discussionmentioning
confidence: 99%